Analysis of the DNA sequence of the putative ABC transporter NCU09975 in Neurospora crassa strains carrying acriflavin resistance markers. - Aric E. Wiest; Sarah Koch; Kevin McCluskey (Fungal Genetics Reports, 2012)
Genomic DNA sequence was determined for the putative Neurospora crassa ABC transporter NCU09975 from several different classical mutant strains including several acriflavin resistant mutants. The sensitivity of these strains to acriflavin was tested. While the open reading frame NCU09975 has multiple polymorphisms in strains sequenced for other purposes, none of the acriflavin resistant classical mutants tested had polymorphisms in the NCU09975 coding region or in the 195 bases upstream of the translation start site.